Availability, Accessibility, and Utilization of Intelligent Tutoring System for Instruction Among Secondary School Teachers in Ilorin, Kwara State, Nigeria - Kehinde Muritala Nuhu; Amos Ochayi Onojah (Indonesian Journal of Multidiciplinary Research, 2022)
The concept of Intelligent Tutoring System (ITS) is used to describe any computer-based educational systems that provide immediate and personalized instruction and feedback to learners, usually without the intervention from a human teacher. This study examined the availability, accessibility, and utilization of ITS applications for teaching among selected secondary schools in Ilorin, Kwara state. The research was a descriptive type using the survey method. A random sampling technique was used to select 150 teachers from 5 secondary schools in Ilorin, Kwara state. Intelligent tutoring systems are not available to secondary school teachers in the Ilorin metropolis; the reaction of the respondents towards the use of ITS application software for instruction was Positive. From the findings of this study, it was concluded that Teachers do not have access to ITS application for instruction as a result of the availability of ITS instruction application. The implication is that if teachers have access to the ITS application for Instruction it will further foster education security. The study recommends that Government and School administrators should ensure adequate power supply and Internet facilities for easy access and utilization of ITS applications for Instruction in the classroom, also teachers who are not in ICT compliance should be encouraged to study further to meet up with the current technological trends.